29.29.11 problem 833

Internal problem ID [5416]
Book : Ordinary differential equations and their solutions. By George Moseley Murphy. 1960
Section : Various 29
Problem number : 833
Date solved : Monday, January 27, 2025 at 11:21:33 AM
CAS classification : [[_homogeneous, `class G`]]

\begin{align*} 2 {y^{\prime }}^{2}-2 x^{2} y^{\prime }+3 y x&=0 \end{align*}

Solution by Maple

Time used: 0.059 (sec). Leaf size: 77

dsolve(2*diff(y(x),x)^2-2*x^2*diff(y(x),x)+3*x*y(x) = 0,y(x), singsol=all)
 
\begin{align*} y \left (x \right ) &= \frac {x^{3}}{6} \\ y \left (x \right ) &= \frac {\sqrt {6}\, \sqrt {-c_{1} x}\, x}{3}+c_{1} \\ y \left (x \right ) &= -\frac {\sqrt {6}\, \sqrt {-c_{1} x}\, x}{3}+c_{1} \\ y \left (x \right ) &= -\frac {\sqrt {6}\, \sqrt {-c_{1} x}\, x}{3}+c_{1} \\ y \left (x \right ) &= \frac {\sqrt {6}\, \sqrt {-c_{1} x}\, x}{3}+c_{1} \\ \end{align*}

Solution by Mathematica

Time used: 0.646 (sec). Leaf size: 146

DSolve[2 (D[y[x],x])^2-2 x^2 D[y[x],x]+3 x y[x]==0,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} \text {Solve}\left [\frac {1}{3} \log (y(x))-\frac {2 \sqrt {x^4-6 x y(x)} \text {arctanh}\left (\frac {x^{3/2}}{\sqrt {x^3-6 y(x)}}\right )}{3 \sqrt {x} \sqrt {x^3-6 y(x)}}&=c_1,y(x)\right ] \\ \text {Solve}\left [\frac {2 \sqrt {x^4-6 x y(x)} \text {arctanh}\left (\frac {x^{3/2}}{\sqrt {x^3-6 y(x)}}\right )}{3 \sqrt {x} \sqrt {x^3-6 y(x)}}+\frac {1}{3} \log (y(x))&=c_1,y(x)\right ] \\ y(x)\to \frac {x^3}{6} \\ \end{align*}